Liquid-liquid phase separation regulates alpha-synuclein aggregate and mitophagy in Parkinson’s disease - Hou, Kaiying; Liu, Tingting; Li, Jingwen; Xian, Meiyan; Sun, Lin; Wei, Jianshe (Frontiers in Neuroscience, 2023)
Parkinson's disease (PD) is the second most common neurodegenerative disease in the world, and alpha-synuclein (α-syn) abnormal aggregate and mitochondrial dysfunction play a crucial role in its pathological development. Recent studies have revealed that proteins can form condensates through liquid-liquid phase separation (LLPS), and LLPS has been found to be widely present in α-syn aberrant aggregate and mitophagy-related protein physiological processes. This review summarizes the occurrence of α-syn LLPS and its influencing factors, introduces the production and transformation of the related protein LLPS during PINK1-Parkin-mediated mitophagy, hoping to provide new ideas and methods for the study of PD pathology.